INTEGRASI PENDIDIKAN AGAMA ISLAM DENGAN ARTIFICIAL INTELLEGENCE, BIG DATA DAN HYPERKONEKTIFITAS DIGITAL - Muhammad Azhari; Syaifuddin Sabda; Hamdan; Husnul Yaqin (ADDABANA: Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the concept and implications of integrating Islamic Religious Education with digital technology, particularly artificial intelligence, big data, and digital hyperconnectivity, in the context of contemporary education. Rapid technological development has significantly transformed learning patterns, access to knowledge, and the relationship between teachers and students, requiring a paradigm shift in religious education to remain relevant without losing its spiritual and moral foundations. This research employs a qualitative approach using library research methods. Data were collected through a systematic review of scientific books, academic journals, research reports, and policy documents related to Islamic education and digital transformation. Data analysis was conducted using an interactive model consisting of data reduction, data display, and reflective-conclusive analysis. The findings reveal that the integration of Islamic Religious Education with artificial intelligence enables more personalized, adaptive, and effective learning through intelligent recommendation systems, religious chatbots, and learning behavior analytics. The use of big data helps educational institutions map students’ moral and religious tendencies more accurately, while digital hyperconnectivity creates global and interactive spaces for religious learning. However, the study also identifies ethical challenges related to the validity of religious sources, the risk of technological dependency, and the potential weakening of spiritual depth. Therefore, the ideal integration is one that positions technology as a means of support, while maintaining the core values of tawhid, adab, and moral character as the primary foundation of Islamic education.